Subcellular Singlet Oxygen and Cell Death: Location Matters - Liang, Pingping; Kolodieznyi, Dmytro; Creeger, Yehuda; Ballou, Byron; Bruchez, Marcel P. (Frontiers in Chemistry, 2020)
We developed a tool for targeted generation of singlet oxygen using light-activation of a genetically encoded fluorogen activating protein complexed with a unique dye molecule that becomes a potent photosensitizer upon interaction with the protein. By targeting the protein receptor to activate this dye in distinct subcellular locations at consistent per-cell concentrations, we investigated the impact of localized production of singlet oxygen on induction of cell-death. We analyzed light dose-dependent cytotoxic response and characterized the apoptotic vs necrotic cell death as a function of subcellular location, including the nucleus, the cytosol, the endoplasmic reticulum, the mitochondria and the membrane. We find that different subcellular origins of singlet oxygen have different potencies in cytotoxic response and the pathways of cell death, and we observed that CT26 and HEK293 cell lines are differentially sensitive to mitochondrially localized singlet oxygen stresses. This work provides new insight into the function of type II reactive oxygen generating photosensitizing processes in inducing targeted cell death and raises interesting mechanistic questions about tolerance and survival mechanisms in studies of oxidative stress in clonal cell populations.